Numerical study of MHD natural convection in a rectangular enclosure with an insulated block. (19th May 2017) - Son, Jong Hyeon; Park, Il Seouk
ABSTRACT: The present study numerically investigates the two-dimensional laminar natural convection in a differently heated rectangular enclosure with an insulated square block, in the presence of a uniform magnetic field applied in the horizontal direction. Numerical simulations were performed for the conditions of different Rayleigh and Hartmann numbers with a fixed Prandtl number. The heat transfer rate decreases with the increase in the intensity of the magnetic field. It was found that the insertion of an insulated block contributes to the enhancement of the heat transfer rate in certain ranges of the block size and the Hartmann number.